Translation techniques of bilingual abstract 'sentrinov' program book - Ade Irma Khairani (Politeknik Negeri Bali, 2019)
This research focuses on a translation technique found in the text of abstract bilingual Indonesian – English that has been translated by the researchers in the Sentrinov Program Book 2018 in Bali. The data analyzed in this study are clauses and their constituents in both Indonesian and English sentences. The source language is in Bahasa Indonesia and the target language is in English. There are a totally of 358 abstract texts, which divided into 13 non-translated ID abstract texts; and 345 in translated ID-EN abstract texts, and there are 287 in translated ID-EN abstract texts which have been as the source data and identified their translation techniques. The objectives of this study are (1) to describe the translation techniques that are applied by the researchers in translating the abstract texts from the source language to the target language and (2) to identify the most dominant and significant translation technique that is used by the researchers. The results identify that the frequency of applying the translation techniques is dominantly used by harafiah (literal translation) in the frequency of 278 (43.6%), then the second place is borrowing (pure/naturalized translation) in the frequency of 138 (21.6%), while the third technique is reduction in the frequency of 58 (9.1%), the fourth technique is creation discursive in the frequency of 54 (8.4%), the fifth technique is calque in the frequency of 28 (4.3%), the sixth technique is amplication in the frequency of 23 (3.6%), the seventh technique is established equivalent in the frequency of 22 (3.4%), the eighth technique is deletion in the frequency of 15 (2.3%), the ninth technique is transposition in the frequency of 12 (1.8%) , and the last technique is addition in the frequency of 9 (1.4%). The finding of this research particularly implies an inlayed innovative translation product and explores the public study for the translation theory.